Suicidal death among autopsied cases in a tertiary care centre in Nepal: a descriptive cross-sectional study - Kunwar, Srijana; Poudel, Aashis; Yadav, Salmalee; Giri, Aashish; Barma, Aachal; Mandal, Manisha; Bajgai, Dinesh (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Globally 10,58,746 suicides occurred in the year 2022. In Nepal, 6792 suicides occurred in the year 2022 according to the data from Nepal Police. Suicide is a public health problem that can be prevented however, the prevention has not been adequately addressed. Our study aimed to find out the prevalence of suicidal death among autopsied cases in the Department of Forensic Medicine and Toxicology of a tertiary care centre in Nepal.Method: A descriptive cross-sectional study was conducted among autopsies in the Department of Forensic Medicine and Toxicology, Patan Hospital, Lalitpur, Nepal. Data from 1 January 2020 to 31 December 2022 was collected after receiving ethical approval from the ethical committee. The point estimate was calculated at a 95% Confidence Interval (CI).Result: Among 665 medico-legal autopsies, the manner of death was found to be suicide in 354 (53.23%) (C.I= 53.19- 53.27, 95% ). Hanging was the most common cause of suicidal death followed by poisoning. Suicidal death was increasing yearly with maximum death in the year 2022(37.01%).Conclusion: The prevalence of suicidal death among autopsied cases was high and the trend was rising.